2016
DOI: 10.1186/s13073-016-0301-4
|View full text |Cite|
|
Sign up to set email alerts
|

Pretreatment gut microbiome predicts chemotherapy-related bloodstream infection

Abstract: BackgroundBacteremia, or bloodstream infection (BSI), is a leading cause of death among patients with certain types of cancer. A previous study reported that intestinal domination, defined as occupation of at least 30 % of the microbiota by a single bacterial taxon, is associated with BSI in patients undergoing allo-HSCT. However, the impact of the intestinal microbiome before treatment initiation on the risk of subsequent BSI remains unclear. Our objective was to characterize the fecal microbiome collected be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
128
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(138 citation statements)
references
References 42 publications
9
128
0
1
Order By: Relevance
“…However, perturbation of the gut microbiome has known causal and predictive roles in human gastrointestinal diseases, particularly in predisposing individuals to infection (31)(32)(33). This suggests there may be a broader role for maintaining keystone gut microbial genetic and functional diversity in the conservation of NHPs, although further research is needed to determine which microbiome perturbations represent dysbiosis, and which are merely benign or even beneficial adaptations to changes in lifestyle and diet.…”
Section: Discussionmentioning
confidence: 99%
“…However, perturbation of the gut microbiome has known causal and predictive roles in human gastrointestinal diseases, particularly in predisposing individuals to infection (31)(32)(33). This suggests there may be a broader role for maintaining keystone gut microbial genetic and functional diversity in the conservation of NHPs, although further research is needed to determine which microbiome perturbations represent dysbiosis, and which are merely benign or even beneficial adaptations to changes in lifestyle and diet.…”
Section: Discussionmentioning
confidence: 99%
“…Montassier and colleagues found that a diverse gut microbiota is associated with protection against chemotherapy-related bloodstream infection 64 .…”
Section: [H2] Phenome Trials and Systems Oncologymentioning
confidence: 99%
“…In fact, several researchers confirm that preventive use of FMT leads to a decreased risk of infectious complications during treatment of hematological diseases [16].…”
Section: Clinical Articlesmentioning
confidence: 99%
“…Colonoflor-16) [8]. Development of the s.c. shotgun next-generation sequencing based on differential analysis of bacterial 16S ribosomal RNA and identification of distinct molecular isolates allowed precise DNA profiling of microbiota composition from donor and recipient, therefore, characterizing the most appropriate fecal donors, and evaluating microbiological results of the treatment [16]. This sequencing procedure consists of 4 successive stages: selection of microbial DNAs from feces, amplification by PCR V4-5 plots of the 16S rRNA gene, sequencing, comparing individual results with a database of previously studied samples, for example, from the NCBI Sequence Read Archive database.…”
Section: Variability Evaluation Of Intestinal Microbiotamentioning
confidence: 99%